Assessment of the quality of drinking water and basic water, sanitation, and hygiene conditions of urban street dwellers in Bangladesh - Dr Zenat Hossain; Md. Harun Or Rashid; Dipan Barai; Najmun Nahar; Dr. Anowara Begum (International Journal of Infectious Diseases)
Background: A substantial portion of the city population of Bangladesh lives on the streets despite economic growth, urbanization, and infrastructure advancements. These people face several public heath challenges such as limited access to safe drinking water, lack of basic sanitation and hygiene practices and lack of access to healthcare. This study aimed to evaluate the quality of the drinking water and examine the basic water, sanitation and hygiene conditions faced by this vulnerable population. Methods: The study was performed as a part of a cross sectional study which was conducted in 13 selected areas of Dhaka city targeting street dwellers without any permanent housing. A total of 84 street people were included in this study and drinking water samples were collected to investigate microbiological quality by assessing Total Coliform (TC) and detecting diarrheagenic bacteria by PCR. A survey was conducted using a semi structure questionnaire to collect data on demographic characteristics, WASH situation and health problems. Results: Findings from drinking water quality assessment showed that 98% (82 of 84) of the water samples were contaminated with coliform bacteria and 40% (34 of 84) samples contained more than 300 TC per 100 ml of water. Genes of Escherichia coli, Salmonella spp., Shigella spp. and Vibrio cholerae were detected in 57%, 8%, 7% and 7% samples respectively. Further analysis on E. coli pathotypic genes revealed that 25% water samples contained genes for EIEC, followed by atypical EPEC (21%) and ETEC (11%). Most of the street people (92%) use public toilets for defecation and 90 % people reported not washing their hands with soap, ash, or sand after using toilets. Only 21% people of this population bath daily. Institutional water sources (surrounding public universities, hospitals, offices etc.) serve as a drinking water collection point for 49% of the street people, followed by DWASA distribution pump (25%). Thirty seven percent people reported experiencing illness within the last 15 days and among them 55% and 32% experienced fever and diarrhea respectively. Discussion: The presence of high levels of total coliform and pathogenic organisms in drinking water samples indicates potential health risks to the street people. Improper collection method, handling, storage of drinking water, challenges, and gaps in access to basic sanitation and hygiene facilities of these street dwellers may cause the contamination of water and other serious infectious disease threats. Conclusion: This study recommends the necessity of improved access to clean water sources and bathing facilities, along with hygiene promotion activities, to address the health challenges of this vulnerable group of population.